Feasibility, safety and benefit of no drip after cholecystectomy: a prespective observational study - Shah, JN; Maharjan, SB; Shah, S; Manadhar, K; Shrestha, S; Shrestha, A; Piya, R; Basnet, NB (Health Renaissance, 2012)
Background: traditionally intravenous fluid is continued after cholecystectomy till resumption of oral intake. This practice seems unnecessary given the fast recovery following uncomplicated cholecystectomy. Objective: To observe feasibility, safety and benefit of no drip after cholecystectomy. Methods: After ethical approval, one hundred cholecystectomy patients were prospectively enrolled in the study. Complicated gall stones were excluded. In consultation with anesthetists, intravenous fluid was calculated based on body weight, maintenance etc. and infused till completion of surgery. Drip was discontinued. Patients were shifted out of operation room with IV lock. Nurses, family members and patients were detailed about this change in practice. Patients were monitored as per our existing standard practice. Anesthetists compulsorily signed out patients to the ward. After 4 hours of surgery patients were encouraged to start oral fluid. Data on fluid requirement, post operative complications and satisfaction of patients were analyzed. Results: One hundred cholecystectomy patients were studied. Average age was 39.8 years, weight 57 kg. Female were 85. Elective cases were 86 and acute 14. Average surgery time was 66 minutes and fluid required was 1313 ml. Open cholecystectomy was 71, laparoscopic 28 and 1-conversion. One laparoscopic patient was reopened due to bleeding. Four patients required drip, 2 for low blood pressure, 1 for vomiting and 1 for low oral intake. There was no mortality in this series. All concerned welcomed this change in practice. Conclusion: discontinuing intravenous drip after uncomplicated cholecystectomy is safe, and well accepted by all concerned. DOI: http://dx.doi.org/10.3126/hren.v10i3.7133 Health Renaissance; September-December 2012; Vol 10 (No.3);187-191